IMPLEMENTASI MODEL PEMBELAJARANPEMECAHAN MASALAH DALAM PENDIDIKAN TEKNOLOGI DASAR UNTUK MENINGKATKAN KREATIVITAS SISWA : Penelitian Tindakan Pada Siswa Sltp Taruna Baku Bandung - Syariful M. (2013)
In this research, pattern of the teaching which conducted by teacher in Basic Technology Education at Junior High School more emphasize on understanding and skill than cognitive ability of the Student. This conditions have negative impact to the thinking pattern development and obstacles the creativity of the Student in overcoming basic technology problems. Technology introduction to the Student of Junior High School naturally have objective not only the Student's understanding, but also how the Student solve technology problem logically. By using action research method which conducted at second grade of Junior High School Taruna Bakti Bandung, researcher attempted to improve the process of learning activity in basic technology. This research more emphasizedat improvement of implementation of problem solving teaching model which focused on learning design, the implementation of problem solving model which have been designed, the implication to the creativity component of the Student and obstacles in its implementation. Considering to the pre-survey results which have been produced many kinds description characteristics of Student, Teacher, material and facility, and the guidance of implementation of Basic Technology Education which have been developed by PPPG Teknologi Bandung, the Teacher has to prior design learning which in it included objective state , implementation strategy, and evaluation. In it implementation the Teacher using it in three steps, that are confrontation, inquiry, and transfer steps. Measurement the impact of problem solving to the creativity of the Student used Torrance creativity test including four element that are fluency, flexibility, originality, and elaboration. From the results of observation which conducted continuously and discuss it the evaluation of implementation to the Teacher, found that every thing need to improved in problem solving learning' implementation, that is the urgently of understanding conceptually which have to had by Teachers ofthe problem solving learning model, curriculum which included teaching aim state, content structure, and facility improvement. Based on the class action research results found that less in the level of divergent thinking ability of the Student as the element of the creativity in problem solving learning process which implemented before class action research conducted. After it implemented found that increasing significantly in the creativity elements ofthe Student (as shown in table 15).